Solar cell packaging adhesive film and preparation method thereof

By using bismuth lanthanum co-doped thorphthalate and ethylene-vinyl acetate copolymer in the solar cell packaging film, the problem of efficiency attenuation of solar cell cells under ultraviolet radiation is solved, and the energy conversion efficiency of solar cell is improved Effect.

CN119463728APending Publication Date: 2025-02-18华能(嘉峪关)新能源有限公司 +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411690433.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

Solar cells will cause significant attenuation of battery efficiency under ultraviolet light radiation. The existing packaging film cannot effectively reduce the incidence of ultraviolet light, resulting in a decrease in battery efficiency.

Method used

The co-doped bismuth lanthanum oxide is uniformly combined with ethylene-vinyl acetate copolymer to form a solar cell packaging film, effectively absorbing ultraviolet light from sunlight and converting it into visible light, improving the energy conversion efficiency of solar cells.

Benefits of technology

By absorbing and converting ultraviolet light, the energy conversion efficiency of solar cells is significantly improved and the attenuation of battery efficiency is reduced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a solar cell packaging adhesive film and a preparation method thereof, the solar cell packaging adhesive film comprises an ethylene-vinyl acetate copolymer and a light conversion material, the light conversion material comprises bismuth and lanthanum co-doped lutetium oxide, the molecular formula of the bismuth and lanthanum co-doped lutetium oxide is Lu2-x-yBixLayO3, x is 0.01-0.02, and y is 0.01-0.1. The bismuth-lanthanum co-doped lutetium oxide is uniformly compounded with the ethylene-vinyl acetate copolymer, so that ultraviolet light in sunlight can be effectively absorbed and converted into visible light capable of being utilized by a solar cell, and the energy conversion efficiency of the solar cell is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a solar cell encapsulation adhesive film and a preparation method thereof. Background Art

[0002] In actual use, solar cells cannot be placed directly in the air and need to be encapsulated and protected with encapsulation films. The encapsulation film needs to have high light transmittance, good adhesion and excellent aging resistance to play a protective, efficiency-enhancing and insulating role. Encapsulation films usually include ethylene-vinyl acetate copolymers, ethylene-α-olefin copolymers, epoxy resins, etc. However, in actual use, solar cells will cause a significant attenuation of cell efficiency under ultraviolet light irradiation. Therefore, it is necessary to improve the encapsulation film to reduce the ultraviolet light incident on the solar cells and reduce the attenuation of cell efficiency. Summary of the invention

[0003] The present invention is based on the inventor's discovery and understanding of the following facts and problems: During actual use, solar cells will experience significant attenuation of cell efficiency when exposed to ultraviolet light.

[0004] The present invention aims to solve at least one of the technical problems in the related art to a certain extent. To this end, the embodiments of the present invention provide a solar cell encapsulation adhesive film and a preparation method thereof, wherein bismuth and lanthanum co-doped lutetium oxide and ethylene-vinyl acetate copolymer are uniformly compounded, which can effectively absorb ultraviolet light in sunlight and convert it into visible light that can be used by solar cells, thereby improving the energy conversion efficiency of solar cells.

[0005] The embodiment of the present invention provides a solar cell encapsulation film, comprising: ethylene-vinyl acetate copolymer and a light conversion material, wherein the light conversion material comprises bismuth-lanthanum co-doped lutetium oxide, wherein the molecular formula of the bismuth-lanthanum co-doped lutetium oxide is Lu 2-x- y Bi x La y O3, x is 0.01-0.02, y is 0.01-0.1.

[0006] The advantages and technical effects of the solar cell encapsulation film of the embodiment of the present invention are as follows: Bismuth and lanthanum co-doped lutetium oxide are uniformly compounded with ethylene-vinyl acetate copolymer, which can effectively absorb ultraviolet light in sunlight and convert it into visible light that can be used by solar cells, thereby improving the energy conversion efficiency of solar cells. Among them, bismuth and lanthanum co-doped lutetium oxide can increase the intensity of the converted visible light relative to bismuth-doped lutetium oxide materials, thereby further improving the energy conversion efficiency of solar cells.

[0007] In some embodiments, the average particle size of the bismuth-lanthanum co-doped lutetium oxide is 50-100 nm.

[0008] In some embodiments, the mass percentage of vinyl acetate in the ethylene-vinyl acetate copolymer is 25-40%, and the melt index of the ethylene-vinyl acetate copolymer is 10-45 g / 10 min.

[0009] In some embodiments, the mass ratio of the ethylene-vinyl acetate copolymer to the photoconversion material is 100:0.01-3.

[0010] In some embodiments, a cross-linking agent is further included, and the mass ratio of the ethylene-vinyl acetate copolymer to the cross-linking agent is 100:1-3.

[0011] In some embodiments, a silane coupling agent is further included, and the mass ratio of the ethylene-vinyl acetate copolymer to the silane coupling agent is 100:0.01-2.

[0012] In some embodiments, a filler is further included, and the filler includes at least one of silicon oxide, aluminum oxide, and zinc oxide; the mass ratio of the ethylene-vinyl acetate copolymer to the filler is 100:1-5.

[0013] In some embodiments, the thickness of the solar cell encapsulation film is 0.1-2.0 mm.

[0014] The embodiment of the present invention provides a method for preparing a solar cell encapsulation adhesive film, comprising: dispersing ethylene-vinyl acetate copolymer and a photoconversion material in a solvent, ultrasonically treating, then adding a crosslinking agent to react, drying to form a film after the reaction, and obtaining the solar cell encapsulation adhesive film by film pressing. In the embodiment of the present invention, the preparation method is simple, the reaction conditions are mild, and it is suitable for industrial application.

[0015] In some embodiments, the reaction time is 2-6 hours;

[0016] And / or, the drying temperature is not higher than 90°C;

[0017] And / or, the temperature of the lamination is 120-150° C., the pressure of the lamination is 5-15 MPa, and the holding time of the lamination is 5-20 min. DETAILED DESCRIPTION

[0018] Embodiments of the present invention are described in detail below. The embodiments are exemplary and intended to be used to explain the present invention, but should not be construed as limiting the present invention.

[0019] A solar cell encapsulation film according to an embodiment of the present invention comprises: ethylene-vinyl acetate copolymer (EVA) and a light conversion material, wherein the light conversion material comprises bismuth-lanthanum co-doped lutetium oxide, wherein the molecular formula of the bismuth-lanthanum co-doped lutetium oxide is Lu 2-x-y Bi x La y O3, x is 0.01-0.02, y is 0.01-0.1.

[0020] The solar cell encapsulation adhesive film of the embodiment of the present invention, bismuth and lanthanum co-doped lutetium oxide and ethylene-vinyl acetate copolymer are uniformly compounded, which can effectively absorb ultraviolet light in sunlight and convert it into visible light that can be used by solar cells, thereby improving the energy conversion efficiency of solar cells. Among them, bismuth and lanthanum co-doped lutetium oxide can increase the intensity of the converted visible light relative to bismuth-doped lutetium oxide materials, thereby further improving the energy conversion efficiency of solar cells.

[0021] In some embodiments, the molecular formula of the bismuth-lanthanum co-doped lutetium oxide is Lu 2-x-y Bi x La y O3, x is 0.01-0.02, specifically, x can be 0.01, 0.015, 0.02; y is 0.01-0.1, specifically, y can be 0.01, 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1. In the embodiment of the present invention, by preferably co-doping lutetium oxide with bismuth and lanthanum, lanthanum doping can increase the intensity of the converted visible light, which is conducive to further improving the efficiency of the solar cell.

[0022] In some embodiments, the average particle size of the bismuth-lanthanum co-doped lutetium oxide is 50-100 nm, specifically, for example, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm; the ultraviolet light excitation wavelength range of the bismuth-lanthanum co-doped lutetium oxide is 300-400 nm, specifically, for example, 337 nm or 372 nm, and the emission peak position is at 411 nm and 492 nm.

[0023] In some embodiments, the preparation method of bismuth-lanthanum co-doped lutetium oxide comprises: mixing a urea aqueous solution, a lutetium chloride aqueous solution, a lanthanum chloride aqueous solution, and a bismuth nitrate aqueous solution for reaction, washing and drying after the reaction; and calcining after drying to obtain bismuth-lanthanum co-doped lutetium oxide;

[0024] Optionally, the lutetium chloride aqueous solution, the lanthanum chloride aqueous solution, and the bismuth nitrate aqueous solution are mixed according to the stoichiometric ratio of the bismuth and lanthanum co-doped lutetium oxide; the molar ratio of the lutetium chloride to the urea is 1:0.25-3, specifically, for example, 1:0.25, 1:0.5, 1:1, 1:3;

[0025] Optionally, the mass percentage concentration of the urea aqueous solution is 20-40%, specifically, for example, 20%, 30%, 40%; the concentration of the lutetium chloride aqueous solution is 0.4-0.6M, optionally, 0.5M; the concentration of the lanthanum chloride aqueous solution is 0.4-0.6M, optionally, 0.5M; the concentration of the bismuth nitrate aqueous solution is 0.4-0.6M, optionally, 0.5M;

[0026] Optionally, the mixing is carried out by stirring; the reaction is carried out at 80°C, the reaction time is 3-5h, optionally, 4h; the drying temperature is 40-80°C; the calcination temperature is 1000-1200°C, optionally, 1100°C; the calcination time is 1-3h, optionally, 2h.

[0027] In the embodiment of the present invention, the bismuth-lanthanum co-doped lutetium oxide material is prepared by a urea precipitation method.

[0028] In some embodiments, the mass percentage of vinyl acetate in the ethylene-vinyl acetate copolymer is 25-40%, and the melt index of the ethylene-vinyl acetate copolymer is 10-45 g / 10 min.

[0029] In some embodiments, the mass ratio of the ethylene-vinyl acetate copolymer to the photoconversion material is 100:0.01-3, specifically, for example, 100:0.01, 100:0.1, 100:0.5, 100:1, 100:3.

[0030] In some embodiments, a cross-linking agent is further included. Optionally, the cross-linking agent includes benzoyl peroxide. The mass ratio of the ethylene-vinyl acetate copolymer to the cross-linking agent is 100:1-3, specifically, for example, 100:1, 100:2, 100:3.

[0031] In some embodiments, a silane coupling agent is further included. Optionally, the silane coupling agent includes γ-glycidyloxypropyltrimethoxysilane (KH560). The mass ratio of the ethylene-vinyl acetate copolymer to the silane coupling agent is 100:0.01-2, specifically, for example, 100:0.01, 100:0.1, 100:0.5, 100:1, 100:2. In the embodiment of the present invention, by adding the silane coupling agent, the peel strength and aging resistance of the encapsulation film can be improved.

[0032] In some embodiments, fillers are further included, and optionally, the fillers include at least one of silicon oxide, aluminum oxide, and zinc oxide; the mass ratio of the ethylene-vinyl acetate copolymer to the filler is 100:1-5, specifically, for example, 100:1, 100:2, 100:3, 100:4, 100:5. In the embodiments of the present invention, adding fillers can improve the aging resistance of the encapsulation film.

[0033] In some embodiments, the thickness of the solar cell encapsulation film is 0.1 to 2.0 mm, specifically, for example, 0.1 mm, 0.2 mm, 0.3 mm, 0.4 mm, 0.5 mm, 1.0 mm, and 2.0 mm.

[0034] In some embodiments, the light transmittance of the solar cell encapsulation film is not less than 90%.

[0035] A method for preparing a solar cell encapsulation adhesive film according to an embodiment of the present invention comprises: dispersing ethylene-vinyl acetate copolymer and a light conversion material in a solvent, ultrasonically treating, then adding a cross-linking agent for reaction, drying to form a film after the reaction, and obtaining the solar cell encapsulation adhesive film by film pressing. In the embodiment of the present invention, the preparation method is simple, the reaction conditions are mild, and it is suitable for industrial application.

[0036] In some embodiments, the solvent includes tetrahydrofuran; optionally, the mass ratio of the ethylene-vinyl acetate copolymer to the solvent is 1:5-40, specifically, for example, 1:5, 1:10, 1:20, 1:30, 1:40.

[0037] In some embodiments, a silane coupling agent and / or a filler are further included, and the ethylene-vinyl acetate copolymer, the photoconversion material, the silane coupling agent and / or the filler are dispersed in a solvent.

[0038] In some embodiments, the dispersing is performed by stirring.

[0039] In some embodiments, the power of the ultrasonic treatment is 300-1000W, specifically, for example, 300W, 500W, 800W, 1000W.

[0040] In some embodiments, the reaction time is 2-6 h, specifically, for example, 2 h, 4 h, 6 h; optionally, the reaction is carried out under stirring.

[0041] In some embodiments, the drying temperature is not higher than 90°C, specifically, for example, 40°C, 50°C, 60°C, 70°C, 80°C, 90°C.

[0042] In some embodiments, the lamination temperature is 120-150°C, specifically, for example, 120°C, 130°C, 140°C, 150°C; the lamination pressure is 5-15MPa; the holding time of the lamination is 5-20min; optionally, the lamination is performed using a flat vulcanizer.

[0043] The present invention is described below with reference to specific embodiments. It should be noted that these embodiments are merely illustrative and do not limit the present invention in any way.

[0044] Example 1

[0045] A method for preparing a solar cell encapsulation film comprises: mixing 10g of ethylene-vinyl acetate copolymer and 0.1g of a light conversion material (Lu 1.955 Bi 0.015 La 0.03 O3, x is 0.015, y is 0.03) is stirred and dispersed in 200mL tetrahydrofuran, ultrasonically treated at 300W, and then 0.1g benzoyl peroxide is added and stirred to react for 4h. After the reaction, it is dried at 50°C to form a film, and a flat-plate vulcanizer is used to press the film at 140°C and 10MPa for 15min to obtain a 0.4mm thick solar cell encapsulation adhesive film.

[0046] At a fixed light intensity of 100mW / m 2 , illumination area 110cm 2 In the following test, compared with the ethylene-vinyl acetate copolymer solar cell encapsulation film without adding light conversion materials, the energy conversion efficiency of the solar cell was increased by 0.40%.

[0047] Example 2

[0048] A method for preparing a solar cell encapsulation film comprises: mixing 10g of ethylene-vinyl acetate copolymer and 0.1g of a light conversion material (Lu 1.935 Bi 0.015 La 0.05 O3, x is 0.015, y is 0.05) was dispersed in 200 mL of tetrahydrofuran and ultrasonically treated at 300 W. Then, 0.1 g of benzoyl peroxide was added and stirred to react for 4 h. After the reaction, the film was dried at 50 ° C. and pressed at 140 ° C. and 10 MPa for 15 min using a flat-plate vulcanizer to obtain a 0.4 mm thick solar cell encapsulation adhesive film.

[0049] At a fixed light intensity of 100mW / m 2 , illumination area 110cm 2 In the test, the energy conversion efficiency of solar cells was increased by 0.62% compared with the ethylene-vinyl acetate copolymer solar cell encapsulation film without adding light conversion materials.

[0050] Example 3

[0051] A method for preparing a solar cell encapsulation film comprises: mixing 10g of ethylene-vinyl acetate copolymer, 0.1g of a light conversion material (Lu 1.95 Bi 0.01 La 0.04 O3, x is 0.01, y is 0.04), 0.05g KH560, and 0.1g alumina are stirred and dispersed in 200mL tetrahydrofuran, and ultrasonically treated at 300W. Then, 0.1g benzoyl peroxide is added and stirred to react for 4h. After the reaction, it is dried at 50°C to form a film. A flat plate vulcanizer is used to press the film at 140°C and 10MPa for 15min to obtain a 0.4mm thick solar cell encapsulation film.

[0052] At a fixed light intensity of 100mW / m 2 , illumination area 110cm 2 In the test, the energy conversion efficiency of solar cells was increased by 0.47% compared with the ethylene-vinyl acetate copolymer solar cell encapsulation film without adding light conversion materials.

[0053] Comparative Example 1

[0054] A method for preparing a solar cell encapsulation film comprises: mixing 10g of ethylene-vinyl acetate copolymer and 0.1g of a light conversion material (Lu 1.985 Bi 0.015 O3, x is 0.015, y is 0) was dispersed in 200 mL of tetrahydrofuran and ultrasonically treated at 300 W. Then, 0.1 g of benzoyl peroxide was added and stirred to react for 4 h. After the reaction, the film was dried at 50 ° C. and pressed at 140 ° C. and 10 MPa for 15 min using a flat-plate vulcanizer to obtain a 0.4 mm thick solar cell encapsulation adhesive film.

[0055] At a fixed light intensity of 100mW / m 2 , illumination area 110cm 2 In the following test, the energy conversion efficiency of solar cells was increased by 0.15% compared with the ethylene-vinyl acetate copolymer solar cell encapsulation film without adding light conversion materials.

[0056] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0057] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.

Claims

1. A solar cell encapsulation film, characterized in that: include: Ethylene-vinyl acetate copolymer and light conversion material, wherein the light conversion material comprises bismuth-lanthanum co-doped lutetium oxide, wherein the molecular formula of the bismuth-lanthanum co-doped lutetium oxide is Lu 2-x- y Bi x La y O3, x is 0.01-0.02, y is 0.01-0.

1.

2. The solar cell encapsulation film according to claim 1, characterized in that: The average particle size of the bismuth-lanthanum co-doped lutetium oxide is 50-100 nm.

3. The solar cell encapsulation film according to claim 1, characterized in that: The mass percentage of vinyl acetate in the ethylene-vinyl acetate copolymer is 25-40%, and the melt index of the ethylene-vinyl acetate copolymer is 10-45 g / 10 min.

4. The solar cell encapsulation film according to claim 1, characterized in that: The mass ratio of the ethylene-vinyl acetate copolymer to the light conversion material is 100:0.01-3.

5. The solar cell encapsulation film according to claim 1, characterized in that: The invention also comprises a cross-linking agent, and the mass ratio of the ethylene-vinyl acetate copolymer to the cross-linking agent is 100:1-3.

6. The solar cell encapsulation film according to claim 1, characterized in that: The invention also comprises a silane coupling agent, wherein the mass ratio of the ethylene-vinyl acetate copolymer to the silane coupling agent is 100:0.01-2.

7. The solar cell encapsulation film according to claim 1, characterized in that: The invention also includes a filler, wherein the filler includes at least one of silicon oxide, aluminum oxide and zinc oxide; and the mass ratio of the ethylene-vinyl acetate copolymer to the filler is 100:1-5.

8. The solar cell encapsulation film according to claim 1, characterized in that: The thickness of the solar cell encapsulation film is 0.1-2.0 mm.

9. A method for preparing the solar cell encapsulation adhesive film according to any one of claims 1 to 8, characterized in that: include: The ethylene-vinyl acetate copolymer and the light conversion material are dispersed in a solvent, ultrasonically treated, and then a cross-linking agent is added to react. After the reaction, the film is dried to form a film, and a solar cell encapsulation adhesive film is obtained by lamination.

10. The method for preparing a solar cell encapsulation adhesive film according to claim 9, characterized in that: The reaction time is 2-6h; And / or, the drying temperature is not higher than 90°C; And / or, the temperature of the lamination is 120-150° C., the pressure of the lamination is 5-15 MPa, and the holding time of the lamination is 5-20 min.